The Factors Related to the Incidence of Occupational Accidents in the Production Department - Jingga, Nusavia Astra; Alayyannur, Putri Ayuni; W., Y. Denny Ardyamto (International Journal of Psychosocial Rehabilitation, 2020)
Accidents happening in the workplace should be controlled well. In the workers in the informal sector, especially in the metal sector, in the manufacturing process has a high risk to have an occupational accident. This study aimed at analyzing the relationship between Lack of Control and the human factor, human factor and Immediate Causes, Immediate Causes and occupational accidents in the manufacturing process of the informal sector in the metal sector. The research design was a cross-sectional study using the observational quantitative method. The population of this study was 18 workers. The sampling method was done by using total sampling with a total sample of 18 workers. The research variable consisted of the lack of control, basic causes, immediate causes, and the incidence of an occupational accident. The data collection was done using questionnaires. Further, the data were analyzed by using Pearson’s correlation test. OSH policy and the provision of PPE and the individual commitment showed a correlation (p-value0.05). The Lack of Control and OSH knowledge and work stress showed no correlation (p- value> 0.05). The human factor and work behavior also showed no correlation (p-value> 0.05). Meanwhile, the behavior and work environment and occupational accidents also showed no correlation (p-value> 0.05). The conclusion of this study are the factors that are correlated to each other are only the OSH policy and the provision of PPE towards individual commitment.